Exploring the Motivational Drivers of Young Adults with Diabetes for Participation in Kidney Research. (November 2022) - Mohini, P; Palaganas, M; Elia, Y; Motran, L; Sochett, E; Curtis, J; Scholey, JW; McArthur, L; Mahmud, FH
Understanding motivational drivers and barriers to patient participation in diabetes research are important to ensure research is relevant and valuable. Young adults with type 1 diabetes (T1D) completed a 31-question qualitative survey evaluating participant experience, understanding, and motivators and barriers to research involvement. A total of 35 participants, 19–28 years of age, 60% female, completed the survey. Motivating factors included personal benefit, relationship with the study team, curiosity, financial compensation, altruism, and nostalgia. Older participants (>22 years) reported higher levels of trust in the study team (p = 0.02) and their relationship with the study team positively influenced their decision to participate (p = 0.03). Financial compensation was a strong motivator for participants with higher education (p = 0.02). Age, sex, education level, and trust in the study team influenced participants' understanding. Barriers included logistics and lack of familial support. Important motivational drivers and barriers to participation in research by young adults with T1D must be considered to increase research engagement and facilitate the discovery of new knowledge.